Temporal dependence between hibernation and posthibernation period according to biochemical profile of hemolymph in Helix pomatia Linnaeus, 1758 - Suljević, Damir; Muhić, Alisa; Islamagić, Erna; Fočak, Muhamed (Acta Biologica Szegediensis, 2017)
The first data regarding protein and mineral concentration during hibernation were obtained in the species Helix pomatia. Total proteins, albumins, globulins, Ca2+ and K+ concentrations were measured at the beginning of hibernation, end of hibernation and posthibernation period (control group). Hemolymph was collected from the pericardial cavity. Total proteins were analyzed using the Biuret method, albumins were analyzed by BCG method, while calcium and potassium concentrations were obtained by CPC method and turbidimetric method, respectively. During hibernation the total protein, globulin and calcium levels were decreased, while the concentration of potassium was evidently increased. Total protein, globulin and calcium levels had the highest values in post-hibernation period. Exceptionally high values were obtained for calcium and globulin concentrations. Significant positive correlation between protein and globulin levels was established. Protein synthesis is the energy-utilizing process during metabolic depression and in our study decreasement of protein concentration in general has been shown during hibernation period.